Tingkat Kecemasan dan Kualitas Tidur Perawat di Masa Pandemi COVID-19 - Vernando Yanry Lameky; Ireine Tauran (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Coronavirus (COVID-19) is an infectious disease caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) which attacks the respiratory system, causing the death of many health workers, including nurses. This raises a level of anxiety that greatly affects the sleep quality of nurses during the COVID-19 pandemic. The purpose of this study was to determine the relationship between anxiety levels and nurses' sleep quality during the COVID-19 pandemic. The design of this study was cross-sectional. The research subjects were 20 nurses who were selected using the total population sampling technique. Data were collected through the Hamilton Rating Scale for Anxiety (HRS-A) and Pittsburgh Sleep Quality Index (PSQI) questionnaires. Data were analyzed using Chi-square test. The results showed that 45% of nurses had very severe anxiety, with poor sleep quality. The results of the analysis showed p-value = 0.021. Furthermore, it was concluded that there was a significant relationship between anxiety levels and nurses' sleep quality.Keywords: COVID-19; nurse; worry; sleep quality ABSTRAK Coronavirus (COVID-19) adalah penyakit menular yang disebabkan oleh virus severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) yang menyerang sistem pernapasan telah menyebabkan banyak tenaga kesehatan yang gugur termasuk perawat. Hal ini menimbulkan tingkat kecemasan yang sangat mempengaruhi kualitas tidur perawat di masa pandemi COVID-19. Tujuan penelitian ini adalah untuk mengetahui hubungan antara tingkat kecemasan dengan kualitas tidur perawat di masa pandemi COVID-19. Desain penelitian ini adalah cross-sectional. Subyek penelitian adalah 20 perawat yang dipilih dengan teknik total population sampling. Data dikumpulkan melalui pengisian kuesioner Hamilton Rating Scale for Anxiety (HRS-A) dan Pittsburgh Sleep Quality Index (PSQI). Data dianaisis menggunakan uji Chi-square. Hasil penelitian menunjukan bahwa 45% perawat memiliki kecemasan sangat berat, dengan kualitas tidur buruk. Hasil analisis menunjukka p-value = 0,021. Selanjutnya disimpulkan bahwa ada hubungan yang signifikan antara tingkat kecemasan dengan kualitas tidur perawat.Kata kunci: COVID-19; perawat; kecemasan; kualitas tidur